(untitled) (Al-Aasar, 2025)
The Holy Qur’an is a great gift from Allah Almighty to the Muslim Ummah. Within it are accounts of past nations and prophecies about future events. It also contains detailed narratives of incidents that occurred among various peoples. The Qur’an is the ultimate criterion between truth and falsehood, and there is no trace of falsehood within it. Whoever does not act upon it or seeks a path other than what it guides to, Allah Almighty removes such a person from the face of existence. To make the Qur’an more understandable and accessible to people—and to elevate or diminish the perceived value of certain ideas or entities—various literary methods have been employed. Among these methods is the use of similes and parables (tashbīh wa tamthīl), whereby a concept is explained through a comparison or example. This technique helps embed the message more firmly in the mind of the listener. Statements presented in the form of examples arouse interest and enable the audience to grasp the intended meaning more quickly.In the forthcoming article, we have presented several parabolic and metaphorical examples from the Holy Qur’an.